Pemanfaatan Limbah Ikan Sebagai Bahan Baku Pakan Buatan Dan Pengaruhnya Terhadap Performa Pertumbuhan Ikan Patin (Pangasius sp.) - Anggela Opsi Yantri Gulo (CV. SINAR HOWUHOWU, 2026)
The availability of quality feed at efficient production costs remains a major challenge in catfish (Pangasius sp.) aquaculture, given that feed accounts for the largest proportion of total aquaculture production costs. This study aimed to evaluate the physical characteristics of fish meal and formulated feed produced from processed fish waste, as well as to analyze the growth performance of catfish fed this formulated diet over a 10-week rearing period. Fish meal was produced from waste materials including heads, bones, skin, and residual flesh through washing, steaming, drying, grinding, and sieving stages, then formulated into pelleted feed together with rice bran, tofu dregs, tapioca flour, and vitamins. The results showed that the fish meal was grayish-brown in color, dense yet slightly coarse in texture, sufficiently dry, and suitable for use as a feed raw material. The resulting formulated feed was in pellet form, stable in water, and suitable for feeding to fish. Over the 10-week rearing period using this feed, the average body weight of catfish increased from 4.90 g to 8.90 g (absolute weight gain of 4.00 g; specific growth rate/SGR of 6.63% per week), total length increased from 9.20 cm to 11.09 cm, and standard length increased from 7.34 cm to 9.26 cm, with the SL/TL ratio remaining relatively stable in the range of 0.76-0.87. These results indicate that formulated feed derived from fish waste is able to adequately support catfish growth, while also offering an economical and sustainable alternative for small-scale fish farmers.